Komparasi Bibliometrik Perkembangan Kajian Agama Islam Dan Kristen: Analisis Tren Dan Dampak Penelitian - Mudrikah, Azizah; Arqom Kuswanjono (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to conduct a bibliometric comparison of Islamic and Christian studies and Trend and Impact Analysis. The literature search was conducted using Dimensions, using the keywords “Islam and Christian.” The articles obtained were then imported into Mendeley software version 1.19.6 to check the completeness of the attributes of each article. The number of articles that met the criteria and continued in the following analysis stage amounted to 478. The bibliometric database was analyzed using the Bibliometrix package in R software version 4.4.1 and VOSviewer version 1.6.20. Analysis through the VOSviewer software showed that the dominant topics in the literature include theological and socio-political relations between Islam and Christianity. New trends are emerging, including gender issues and geopolitical dynamics in Africa and Asia. The level of international collaboration in this research reaches around 20%, with the most significant contribution coming from Indonesian institutions, especially universities based on Islamic studies.